The High-Dose of Exogenous Melatonin Did Not Alter the Sleep-Wake Cycle in Anoxic Brain Injury Patients - Mikhail Kanarskii; Julia Nekrasova; Pranil Pradhan; Ilya Borisov; Olga Korepina; Ekaterina Kondratyeva; Angelina Nikitkina; Marina Petrova (Sleep Medicine Research, 2022)
Disturbance in circadian rhythms and the sleep-wake cycle is typical for patients in the intensive care unit, which retards rehabilitation. To assess the effect of exogenous melatonin and simultaneous mitigation of intensive care unit environmental factors on sleep duration. We studied five patients with chronic disorder of consciousness caused by anoxic brain injury. In addition, we varied the level of melatonin secretion in blood plasma to assess melatonin’s bioavailability and elimination time. We evaluated the sleep-wake cycle using continuous video-electroencephalogram monitoring with the addition of oculographic and myographic channels for 72 hours. All the patients received melatonin tablets on the second day, wore masks and ear plugs, and had no feeding and nursing manipulations at night on the second and third days. There was no significant difference in sleep time between the first, second, and third days. Future studies of the circadian rhythm should aim at gaining a deeper analysis of the characteristics of the sleep-wake cycle in patients with severe anoxic brain injury together with further research for possible ways to influence the circadian component of sleep.